Performance evaluation of customised asphalt concrete mixture for high-strength pavement application - Lau, Samuel Ming Jun (Nanyang Technological University, 2023)
Singapore is a highly developed urban city facing limited road expansion constraints due to its small size of roughly 728.6km2 with a steadily increasing general population, and consequently a higher number of vehicles on the road, leading to more rapid deterioration of road quality. Thus, resources should be invested into investigating methods to reduce the need for roadworks to save on both opportunity and overall financial cost, one of which strategy would be to increase the strength of pavement to improve its useful life. Herein, roads in Singapore are principally flexible pavement construction with surfacing (wearing and binder courses) of asphalt concrete constituted of bituminous binder and aggregates. Bituminous binder acts as a binding agent of the aggregates to produce asphalt concrete mix. It is also a key component of asphalt that dictates the strength and deformation of the asphalt concrete, therefore the type of bitumen used is important. LTA requires the type of binder to be 60/70 penetration grade, but several options exist in the market with useful properties, such as PG-76 bituminous binder that strengthens the bond between aggregates and binder more efficiently due to its higher viscosity. Another alternative would be epoxy asphalt (EA), known to possess properties such as greater resistance to loads even at higher temperatures, leading to less maintenance in the long run. However, little research has been focused on drawing comparisons between EA and other forms of existing binders, such as the afore-mentioned PG-76 binder. This study evaluated the feasibility of EA as a stronger binder compared to PG-76 bituminous binder. Samples of W3B asphalt concrete wearing courses made using both PG-76 and EA as binders were subjected to several tests to determine overall strength and suitability for pavement application, including long-term aging for EA to simulate aging that the mixture will undergo an assumed service lifespan of 7 to 10 years. The laboratory performance tests included Moisture Susceptibility Test, Dynamic Creep Test, and Indirect Tensile Strength Test. The Marshall Stability Test was also conducted to determine the optimum binder content and derive its stability and flow values. The optimum binder content of the PG-76 and EA specimens was determined to be 6% and 7.25%, respectively. Results of the experiments on both short and long-term aged EA specimens displayed greater Marshall stability and tensile strength from Marshall Test and Indirect Tensile Strength Test respectively, lesser permanent deformation from Dynamic Creep test, yet significantly lesser resistance to moisture damage from the Moisture Susceptibility Test as compared to asphalt concrete specimens using PG-76 Binder. Hence, EA may not be a feasible option for high-strength pavement application from moisture susceptibility consideration.